Hansa-Georga Gadamera i Thrasybulosa Georgiadesa ujęcia przekładu - Orman, Edyta (Investigationes Linguisticae, 2018)
The basis for this research form spontaneous use of the word “translation” sensu largo in informal language and dual dictionary meaning of this word, i.e. “translation” sensu stricto and “expressing”. Article focuses on comparison of translation term usage in philosophical writings by Hans-Georg Gadamer and in musicological writings by Thrasybulos Georgiades. Considering translation in the meaning of “expression” and, at the same time, agreeing that music is a speech of tones, one can accept general connection between script and speech described by the German hermeneutist, as a foundation of detailed relation between musical notation and resounding described by Greek music historian. Interpretation emerges as common for expression and translation, but nonetheless it demonstrates itself differently in case of language and music. Specificity of the art of sounds as compared with the art of words is constituted by the difference between words’ meaning and musical structure. In the end, transcription and transposition inherent to art of sounds and completing Georgiades’s term translation can be regarded as musical translations.